THE SPLIT EQUALITY FIXED POINT PROBLEM FOR DEMI-CONTRACTIVE MAPPINGS - Chidume, C. E.; Ndambomve, P.; Bello, A. U. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2015)
Motivated by the recent work of Moudafi (Inverse Problems, 26 (2010), 587-600) and inspired by Xu (Inverse Problems, 22 (2006), 2021-2034), Censor and Segal (J. Convex Anal. 16 (2009), 587-600), and Yang (Inverse Problems, 20 (2004), 1261-1266), we investigate a Krasnoselskii-type iterative algorithm for solving the split equality fixed point problem recently introduced by Moudafi Moudafi and Al-Shemas (Transactions on Mathematical Programming and Applications, Vol. 1, No. 2 (2013), 1-11). Weak and strong convergence theorems are proved for the class of demi-contractive mappings in Hilbert spaces. Our theorems extend and complement some recent results of Moudafi and a host of other recent important results.